Os contratos empresariais como meio de garantia dos direitos humanos no âmbito das empresas transnacionais - Banhos, Emanuelle Clayre Silva (2022)
Transnational corporations plays an important role today, since they hold greater economic, social and political power than states, and their relations are governed by contracts, which are protected by the Lex Mercatoria. Considering the power of these corporations and how much their actions, whether positive or negative, can reflect on society, especially in the promotion or violation of human rights, became the need to incorporate in their scope of action the adoption of behavior with a humanist bias, through the requirement of conducts that conform to ethical and social values acceptable in their external and internal relations. Therefore, the adoption of these behaviors was reflected in the contractual field due to the modification of the contractual conception, which went from individualistic to one that takes care not only of the reflection of the negotiations between the parties, but also of its reflections in society. Thus, considering that contracts govern business activities, this paper aims to evaluate the use of the business contract as a mean of guaranteeing and promoting human rights in the context of transnational corporations. To this end, the hypothetical-deductive method was used, with a bibliographical research as a methodological procedure. As conclusions, it was found that the nineteenth-century conformation of contract, founded on equality and unrestricted freedom, no longer meets the yearnings of today's society, since the current contract conception follows in the sense that it serves for the promotion of human dignity and the rights inherent to it, in balance with the market. Given the prominent role held by transnational corporations in today's society, there is a need for their performance in favor of society's values, and not only in function of profit. Finally, the business contract is an instrument of humanism, and a mean of regulating the global market, while the insertion, explicitly or implicitly, of humanist values in its content can contribute to the guarantee and promotion of human rights, in addition to enabling the harmonious coexistence of human rights and business, and the realization of humanist capitalism.